The sixties in America Volume 2 - Singleton, Carl.; Wildin, Rowena, 1956- (Pasadena, Calif. : Salem Press, 1999)
The Sixties in America surveys the events and people of the 1960's. The set not only provides in-depth coverage of all aspects of the three major events of the 1960's that give the decade its distinctive character-but also surveys important developments in the arts, science and technology, business and the economy, government and politics and gender issues. The set looks at the most important people and events in the arts, media, music and sports and covers the headline-grabbing news items of the period.
v. 1. Abernathy, Ralph-Ginsberg, Allen -- v. 2. Giovanni, Nikki-SANE (National Committee for a Sane Nuclear Policy) -- v. 3. School desegregation-Zappa, Frank.
Includes bibliographical references and index.
85382
Keywords: United States -- History -- 1961-1969 -- Encyclopedias